2020
DOI: 10.1021/acsami.9b22690
|View full text |Cite
|
Sign up to set email alerts
|

Improved Interface Stability and Room-Temperature Performance of Solid-State Lithium Batteries by Integrating Cathode/Electrolyte and Graphite Coating

Abstract: Poor interface stability is a crucial problem hindering the electrochemical performance of solid-state lithium batteries. In this work, a novel approach for interface stability was proposed to integrate the cathode/ solid electrolyte by forming an electrolyte buffer layer on the rough surface of the cathode and coating a layer of graphite on the side of the electrolyte facing the lithium anode. This hybrid structure significantly improves the integration and the interface stability of the electrode/electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…[1][2][3] As solid-state electrolytes have the advantages of higher energy density, wider potential window, longer cycle life and higher safety factor, they have been paid more attention and are more widely used. 4,5 They can solve many potential dangers caused by the use of flammable and explosive liquid electrolytes in conventional lithium-ion batteries. For example, the liquid electrolytes are prone to internal short circuits, and the volatilization and leakage of solvents limit the commercial application of lithium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] As solid-state electrolytes have the advantages of higher energy density, wider potential window, longer cycle life and higher safety factor, they have been paid more attention and are more widely used. 4,5 They can solve many potential dangers caused by the use of flammable and explosive liquid electrolytes in conventional lithium-ion batteries. For example, the liquid electrolytes are prone to internal short circuits, and the volatilization and leakage of solvents limit the commercial application of lithium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Energy storage equipment has gradually become an integral part of daily life and national development 1‐3 . As solid‐state electrolytes have the advantages of higher energy density, wider potential window, longer cycle life and higher safety factor, they have been paid more attention and are more widely used 4,5 . They can solve many potential dangers caused by the use of flammable and explosive liquid electrolytes in conventional lithium‐ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…But, it should be kept in mind that the ionic conductivity gradient at the interface and bulk should be as minimum as possible. [80,81,83] In the past, Al 2 O 3 , [84] Li 4 Ti 5 O 12 (LTO), [85] LiNbO 3 (LNO), [27,28,86,87] and Li 6.1 La 3 Al 0.3 Zr 2 O 12 (LLAZO) [88] coatings have been done (Figure 6c); however, the decrease in ionic conductivity puts a major strain on the overall cycling performance of the cell. Due to a sharp decrease in ionic conductivities at the buffer layer and SSE interface, diffusion of Li ions will be hindered.…”
Section: Nanoscale Interfacial Engineering At the Cathodementioning
confidence: 99%
“…Artificial coating at the electrode/electrolyte interface is another process to improve the contact and increase the Li + ion flux at the interface 22,23 . Chen et al 24 developed a solid‐state battery with poly(propylene carbonate)‐based polymer electrolyte. A coating of graphite layer was performed at the anode/electrolyte and cathode/electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…A coating of graphite layer was performed at the anode/electrolyte and cathode/electrolyte. They showed that this layer acts as a buffer layer at electrode/electrolyte interface, which decreases the interfacial resistance and blocks the propagation of lithium dendrites 24 . However, this method adds more complexity to the production of such batteries.…”
Section: Introductionmentioning
confidence: 99%